THE READING COMPREHENSION STRATEGIES USED BY THE STUDENTS OF SMAN 3 PEMATANGSIANTAR - Lezly Frisca Sigalingging; Berlin Sibarani; Johannes Jefria Gultom (Universitas Negeri Medan, 2020)
This thesis entitled “The Reading Comprehension Strategies Used by Students of SMA N 3 Pematangsiantar” is designed to investigate the strategies implemented by the students in comprehending the reading texts and the underlying reasons why the students implemented the strategies as they did. Qualitative research design was conducted as the research method in this study. The subjects of this study were 6 students of grade eleventh at SMA N 3 Pematangsiantar in academic year 2017/2018. Three of the students were identified as the students who have high English ability, while the other three students have low English ability. The data were collected by in-depth interview. The data were analyzed by using Miles, Huberman, and Saldana (2014) data analysis technique. The findings of the study showed that the students implemented 4 strategies in comprehending the reading text, they are (1) Experience, (2) Summarize, (3) Re-read, and (4) Look up the words you don’t know. The underlying reasons of the strategies in comprehending the reading text are different for each strategy. The underlying reason for experience strategy is the reading comprehension facilitation, summary strategy is indicator of comprehension, re-read is the cognitive process, and look up the word you do not know is the lack of vocabulary mastery. Key words: Reading, Reading comprehension, strategies